Students team achievement division - Jamaludin, Mazlina; Mokhtar, Muhammad Fauzi (Human Resource Management Academic Research Society, 2018)
Student Team Achievement Division (STAD) is one of the cooperative learning methods that involves small groups in which each member of the group works together on a common task to achieve the common goal. STAD was carried out using Kemmnis and McTaggart’s Participatory Action Theory, among first semester students to evaluate students’ attitude towards tourism geography subject. Achievement test was compared between the experimental group and control group using quasi pretest and posttest via experimental design on the students. Attitude inventory scale and team work satisfaction scale were measured to understand the students’ feedback on STAD teaching technique. The experimental group of STAD students rated highest statement on “My team develops clear collaborative patterns to increase team learning efficiency” (M=4.45, SD=0.73). In team work participation evaluation, the experimental group respondents this statement highest “Interacting with the other members can increase my motivation to learn” (M=4.43, SD=0.73). This research concluded that STAD technique improved students’ achievement test (t-value= 9.01*), attitude and teamwork among the experimental group students.